Solid capacitor and preparation method thereof
By preparing benzofurandione monomer and conductive polymer solution, the problems of low conductivity and poor heat resistance in solid capacitors are solved, and the lead-out rate and heat resistance of solid capacitors are improved. Mass production.
Patent Information
- Application Number
- CN202411494300.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-31
AI Technical Summary
The existing conductive polymers have low conductivity, poor heat resistance, low lead-out efficiency and high impedance in solid-state capacitors, resulting in insufficient performance of solid-state capacitors. The existing technology has not effectively solved these problems.
The A and B liquids are prepared by mixing benzofurandione monomers and conductive polymer solutions. The solid electrolyte is formed by cycling multiple impregnation and drying treatments, which improves the filling rate and conductivity of the conductive polymer on the surface of the oxidized foil and reduces the Plasma impedance, enhances heat resistance.
It realizes high lead-out rate, low ESR and better heat resistance of solid-state capacitors, simplifies production processes, reduces costs, and is suitable for large-scale production.
Smart Images

Figure BDA0005100868640000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic materials and electronic components, and in particular to a solid capacitor and a preparation method thereof. Background Art
[0002] Solid capacitors, usually called solid aluminum electrolytic capacitors, differ from ordinary capacitors (i.e. liquid aluminum electrolytic capacitors) in that they use different dielectric materials. The dielectric material of liquid aluminum capacitors is electrolyte, while the dielectric material of solid capacitors is conductive polymer materials. Solid capacitors usually have the characteristics of high stability, long life, low ESR and high rated ripple current. Currently, there are two main types of commercialized solid aluminum electrolytic capacitors: organic semiconductor aluminum electrolytic capacitors (OS-CON) and polymer conductor aluminum electrolytic capacitors (PC-CON). Among them, solid aluminum polymer chip capacitors are a unique structure formed by combining the characteristics of aluminum electrolytic capacitors and tantalum capacitors. Like liquid aluminum electrolytic capacitors, solid aluminum polymers are mostly in the form of chips. A high-conductivity polymer electrode film is deposited on alumina as the cathode, and carbon and silver are the lead-out electrodes of the cathode, which is similar to the structure of solid tantalum electrolytic capacitors.
[0003] The wound core package solid capacitor is a solid capacitor made by winding the anode foil, cathode foil and diaphragm material (such as electrolytic paper) together to form a core package, and then undergoing a series of process treatments. The cathode electrolyte of this capacitor uses a conductive polymer instead of a traditional electrolyte, which gives it a unique performance advantage. Existing conductive polymers, such as a combination of (3,4-ethylenedioxythiophene monomer) polymer and polystyrene sulfonic acid (PEDOT:PSS), have low material conductivity and poor heat resistance (when used on capacitors, the 125°C load test will cause the capacitor to fail) 、 The lead-out efficiency of capacitors is low and the impedance is relatively high. Due to the defects of existing conductive polymers, the existing technology has not yet made a major breakthrough. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies in the prior art, one of the purposes of the present invention is to provide a method for preparing a solid capacitor, first prepare special A liquid and B liquid respectively, then immerse the wound capacitor core in a pretreatment liquid for surface corrosion protection treatment, and then circulate and immerse in A liquid and B liquid for multiple times and dry, during which a solid electrolyte is formed by reaction and a higher filling rate, thereby obtaining a solid capacitor with high extraction, lower ESR and better heat resistance. The preparation method is simple to operate, easy to control, high in production efficiency, low in production cost, and can be used for large-scale production.
[0005] A second object of the present invention is to provide a solid capacitor having a higher extraction rate, a lower ESR and better heat resistance.
[0006] One of the objectives of the present invention is achieved by the following technical solution: A method for preparing a solid capacitor comprises the following steps:
[0007] (S1), mixing a benzofurandione monomer and a solvent A and heating to dissolve, then adding a conductive polymer solution and stirring evenly to obtain a liquid A;
[0008] (S2), taking the oxidant and the solvent B and mixing them evenly to obtain liquid B;
[0009] (S3), taking the wound capacitor core package, subjecting it to heat drying treatment to remove water, and then placing it in the pretreatment liquid for immersion, the immersion time is 2-10min, taking out the wound capacitor core package and subjecting it to heat drying treatment again to obtain an anti-corrosion core package;
[0010] (S4), immersing the anti-corrosion core package in the liquid A under negative pressure for 1-10 minutes, taking out the anti-corrosion core package, pre-drying it, and then vacuum / air drying it to obtain a core package treated with liquid A;
[0011] (S5), immersing the core package treated with liquid A into the liquid B under negative pressure for 1-8 minutes, and then performing vacuum / air drying to obtain a core package treated with liquid B;
[0012] (S6), steps (S4) and (S5) are recorded as one cycle, and the cycle is performed 2-6 times, and after each cycle, the core is immersed in ethanol for 3-8 minutes, and then vacuum / air drying is performed to obtain a solid capacitor.
[0013] The preparation method of the solid capacitor of the present invention comprises the following steps: firstly, a benzofurandione monomer, a solvent A and a conductive polymer solution are mixed to prepare a liquid A, and an oxidant and a solvent B are mixed to prepare a liquid B. Then, a wound capacitor core is immersed in a pretreatment liquid for surface anticorrosion protection treatment, and a protective layer is formed on the surface of an oxide foil (usually an aluminum oxide foil) of the wound capacitor core package, so as to effectively prevent the subsequent reaction of the liquid A and the liquid B from corroding and damaging the oxide foil, thereby causing a high leakage current. Then, the wound capacitor core is immersed in the liquid A and the liquid B for multiple times and dried, respectively immersed in the liquid A and then dried, and immersed in the liquid B and then dried, so as to prevent the occurrence of corrosion in the wound capacitor core package. The reaction occurs during the immersion process or before the impregnation, which affects the extraction effect and the storage stability of the solution. The AB alternating and repeated impregnation is to allow the benzofurandione monomer and the oxidant to react inside the wound capacitor core package, and the conductive polymer grows in situ in the core package to increase the filling rate of the conductive polymer on the surface of the oxide foil, thereby increasing the extraction rate and the conductive polymer has a higher conductivity (up to 2000S / cm) and a higher thermal decomposition temperature (up to 380°C), which is more conducive to reducing ESR and improving heat resistance, and obtaining a solid capacitor with high extraction, lower ESR and better heat resistance. In step (S6), after each cycle, the core package is completely immersed in anhydrous ethanol to clean and remove the oxidant, effectively avoiding the next cycle from reacting during or before the impregnation process to affect the extraction effect and the filling rate of the conductive polymer on the surface of the oxide foil. Because the wound capacitor forms a polymer negative electrode layer (cathode electrolyte) inside the core package by adsorbing liquid A and liquid B by a diaphragm material (such as electrolytic paper) and then drying and polymerizing; and there is no adsorption material on the surface of the laminated capacitor, the liquid A and liquid B used in the present invention are difficult to be adsorbed on the surface of the capacitor to form an effective negative electrode layer, resulting in failure to achieve effective extraction, and are not suitable for laminated capacitors, especially for wound capacitors. In addition, step (S6) records steps (S4) and (S5) as one cycle, wherein step (S4) is continuously operated at least once, and step (S5) is continuously operated at least once.
[0014] Preferably, in the step (S3), the immersion height of the wound capacitor core package is lower than one third to one half of the distance from the top of the wound capacitor core package, the heat drying treatment is air drying at 150°C for 25-50 minutes, and the heat drying treatment again is air drying at 150°C for 25-50 minutes.
[0015] By adopting the above technical solution, the pretreatment liquid penetrates into the wound capacitor core package and forms an anti-corrosion protective layer to prevent the corrosion damage of the oxide foil by the reaction intermediates in the subsequent in-situ polymerization process, and the dielectric layer is damaged or thinned, thereby causing the defect of high leakage current. Further, the pretreatment liquid is a PVDF solution, a polypropylene resin solution or a fluorocarbon resin solution.
[0016] Preferably, in the step (S4), the immersion height of the anti-corrosion core package is lower than one-third to one-half of the distance from the top of the anti-corrosion core package, and the immersion condition is a negative pressure of -0.06 to -0.09 MPa; when the anti-corrosion core package is taken out after impregnation, the droplets hanging on the bottom of the anti-corrosion core package are scraped off; the pre-drying treatment is pre-drying at 60°C with forced air for 5-20 minutes; the vacuum / force air drying treatment is drying at 80-150°C in a vacuum / force air drying oven for 10-50 minutes.
[0017] By adopting the above technical solution, the benzofurandione monomer and the conductive polymer are infiltrated into the anti-corrosion core package, and the excess solvent is dried to remove and the benzofurandione monomer and the conductive polymer are attached to the inside of the anti-corrosion core package. The impregnation liquid enters the core package by adsorption. If the core package is immersed too high and too much impregnation liquid is immersed, it is easy to cause the impregnation liquid to climb to the core package guide pin, thereby causing a short circuit and a surge in leakage current.
[0018] Preferably, in the step (S5), the impregnation height of the core package treated with liquid A is the same as the impregnation height in step (S4), and the immersion condition is a negative pressure of -0.06 to -0.09 MPa; the vacuum / air drying treatment is carried out in a vacuum / air drying oven at 60-125°C for 5-50 minutes.
[0019] By adopting the above technical solution, the oxidant is infiltrated into the core package treated with liquid A, and the conductive polymer is polymerized and grown in situ inside the core package during the vacuum drying process, while removing excess solvent. When impregnated with liquid A and liquid B, the negative pressure is -0.06 to -0.09MPa, which effectively increases the filling degree of the conductive polymer inside the core package, is more conducive to reducing ESR and improving heat resistance, and obtains a solid capacitor with high lead-out, lower ESR and better heat resistance.
[0020] Preferably, in the step (S6), the vacuum / air drying treatment is carried out in a vacuum / air drying oven at 60-150° C. for 5-20 min.
[0021] The above technical solution is adopted to remove excess ethanol.
[0022] Preferably, the benzofurandione monomer is 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione; the solvent A is at least one of dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile and propylene carbonate; the conductive polymer solution is a PBFDO-dimethyl sulfoxide solution, PBFDO-N,N-dimethylacetamide solution, PBFDO-N,N-dimethylformamide solution or PBFDO-N-methylpyrrolidone solution with a solid content of 6-15 mg / ml. PBFDO is a conductive polymer poly(benzofurandione).
[0023] Preferably, the mass ratio of the benzofurandione monomer to the conductive polymer is 1-20:1; and the concentration of the benzofurandione monomer after being dissolved in solvent A is 4-25 mg / ml.
[0024] Preferably, the oxidant is at least one of organic quinones, phosphomolybdic acid, peroxides, metal salts, persulfates, metal oxides, non-metallic oxides, perborate and perbenzoic acid compounds.
[0025] According to the technical solution, further, the oxidant is at least one of 2,5-dimethylbenzoquinone, phosphomolybdic acid, hydrogen peroxide, benzoyl peroxide, potassium permanganate, potassium persulfate and sodium perborate.
[0026] Preferably, the solvent B is at least one of dimethyl sulfoxide, ethanol, ethyl acetate, N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, deionized water, acetonitrile and propylene carbonate; and the concentration of the solution B is 2-100 mg / ml.
[0027] The second objective of the present invention is achieved by the following technical solution: a solid capacitor is prepared by the solid capacitor preparation method as described above.
[0028] The beneficial effects of the present invention are as follows: the preparation method of the solid capacitor of the present invention first prepares special A liquid and B liquid respectively, then immerses the wound capacitor core in the pretreatment liquid for surface corrosion protection treatment, and then circulates and immerses in A liquid and B liquid for multiple times and dries, during which a solid electrolyte is formed by reaction with a higher filling rate, and a solid capacitor with high extraction, lower ESR and better heat resistance is obtained. The preparation method is simple to operate, easy to control, high in production efficiency, low in production cost, and can be used for large-scale production.
[0029] The solid capacitor of the present invention has a higher extraction rate, a lower ESR and better heat resistance. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0031] Example 1
[0032] A method for preparing a solid capacitor comprises the following steps:
[0033] (S1), mixing a benzofurandione monomer and a solvent A and heating to dissolve, then adding a conductive polymer solution and stirring evenly to obtain a liquid A;
[0034] (S2), taking the oxidant and the solvent B and mixing them evenly to obtain liquid B;
[0035] (S3), taking the wound capacitor core package, after heat drying to remove water, placing it in the pretreatment liquid for immersion, the immersion time is 6 minutes, taking out the wound capacitor core package and heat drying it again to obtain an anti-corrosion core package;
[0036] (S4), immersing the anti-corrosion core package in the liquid A under negative pressure for 5 minutes, taking out the anti-corrosion core package, pre-drying it, and then vacuum drying it to obtain a core package treated with liquid A;
[0037] (S5), immersing the core package treated with liquid A into the liquid B under negative pressure for 5 minutes, and then performing vacuum drying to obtain a core package treated with liquid B;
[0038] (S6), record one step (S4) and one step (S5) as one cycle, and repeat the operation 4 times. After each cycle, the core is immersed in ethanol for 5 minutes, and then vacuum dried to obtain a solid capacitor.
[0039] In the step (S3), the immersion height of the wound capacitor core package is lower than two-fifths of the distance from the top of the wound capacitor core package, the heat drying treatment is air drying at 150°C for 30 minutes, and the second heat drying treatment is air drying at 150°C for 30 minutes.
[0040] In the step (S4), the immersion height of the anti-corrosion core package is lower than two-fifths of the distance from the top of the anti-corrosion core package, and the immersion condition is a negative pressure of -0.08MPa; when the anti-corrosion core package is taken out after impregnation, the droplets hanging at the bottom of the anti-corrosion core package are scraped off; the pre-drying treatment is pre-drying at 60°C with forced air for 12 minutes; the vacuum drying treatment is drying at 110°C in a vacuum drying oven for 25 minutes.
[0041] In the step (S5), the impregnation height of the core package treated with liquid A is the same as the impregnation height in step (S4), and the immersion condition is a negative pressure of -0.08 MPa; the vacuum drying treatment is drying in a vacuum drying oven at 95°C for 25 minutes.
[0042] In the step (S6), the vacuum drying treatment is carried out by drying in a vacuum drying oven at 100° C. for 10 minutes.
[0043] The benzofurandione monomer is 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione; the solvent A is dimethyl sulfoxide; and the conductive polymer solution is a conductive polymer PBFDO-dimethyl sulfoxide solution with a solid content of 10.6 mg / ml.
[0044] The mass ratio of the benzofurandione monomer to the conductive polymer is 10:1; the concentration of the benzofurandione monomer after being dissolved in solvent A is 15 mg / ml.
[0045] The oxidant is 2,5-dimethylbenzoquinone; and the pretreatment solution is PVDF solution.
[0046] The solvent B is dimethyl sulfoxide; the concentration of the B solution is 20 mg / ml.
[0047] Example 2
[0048] A method for preparing a solid capacitor comprises the following steps:
[0049] (S1), mixing a benzofurandione monomer and a solvent A and heating to dissolve, then adding a conductive polymer solution and stirring evenly to obtain a liquid A;
[0050] (S2), taking the oxidant and the solvent B and mixing them evenly to obtain liquid B;
[0051] (S3), taking the wound capacitor core package, after heat drying to remove water, placing it in the pretreatment liquid for immersion, the immersion time is 3min, taking out the wound capacitor core package and heat drying it again to obtain an anti-corrosion core package;
[0052] (S4), immersing the anti-corrosion core package in the liquid A under negative pressure for 2 minutes, taking out the anti-corrosion core package, pre-drying it, and then vacuum drying it to obtain a core package treated with liquid A;
[0053] (S5), immersing the core package treated with liquid A into the liquid B under negative pressure for 2 minutes, and then performing vacuum drying to obtain a core package treated with liquid B;
[0054] (S6), record one step (S4) and one step (S5) as one cycle, repeat the operation twice, and after each cycle, immerse the core in ethanol for 3 minutes, and then vacuum dry to obtain a solid capacitor.
[0055] In the step (S3), the immersion height of the wound capacitor core package is less than half of the distance from the top of the wound capacitor core package, the heat drying treatment is forced air drying at 150°C for 25 minutes, and the second heat drying treatment is forced air drying at 150°C for 50 minutes.
[0056] In the step (S4), the immersion height of the anti-corrosion core package is lower than half of the distance from the top of the anti-corrosion core package, and the immersion condition is a negative pressure of -0.06MPa; when the anti-corrosion core package is taken out after impregnation, the droplets hanging at the bottom of the anti-corrosion core package are scraped off; the pre-drying treatment is pre-drying at 60°C with forced air for 6 minutes; the vacuum drying treatment is drying at 80°C in a vacuum drying oven for 48 minutes.
[0057] In the step (S5), the impregnation height of the core package treated with liquid A is the same as the impregnation height in step (S4), and the immersion condition is a negative pressure of -0.06 MPa; the vacuum drying treatment is drying in a vacuum drying oven at 70°C for 50 minutes.
[0058] In the step (S6), the vacuum drying treatment is carried out by drying in a vacuum drying oven at 70° C. for 20 minutes.
[0059] The benzofurandione monomer is 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione; the solvent A is N,N-dimethylformamide; and the conductive polymer solution is a PBFDO-N,N-dimethylformamide solution with a solid content of 6 mg / ml.
[0060] The mass ratio of the benzofurandione monomer to the conductive polymer is 2:1; the concentration of the benzofurandione monomer after being dissolved in solvent A is 10 mg / ml.
[0061] The oxidant is hydrogen peroxide; the pretreatment solution is PVDF solution.
[0062] The solvent B is deionized water; the concentration of the B solution is 3 mg / ml.
[0063] Example 3
[0064] A method for preparing a solid capacitor comprises the following steps:
[0065] (S1), mixing a benzofurandione monomer and a solvent A and heating to dissolve, then adding a conductive polymer solution and stirring evenly to obtain a liquid A;
[0066] (S2), taking the oxidant and the solvent B and mixing them evenly to obtain liquid B;
[0067] (S3), taking the wound capacitor core package, after heat drying to remove water, placing it in the pretreatment liquid for immersion, the immersion time is 10 minutes, taking out the wound capacitor core package and heat drying it again to obtain an anti-corrosion core package;
[0068] (S4), immersing the anti-corrosion core package in the liquid A under negative pressure for 10 minutes, taking out the anti-corrosion core package, pre-drying it, and then vacuum drying it to obtain a core package treated with liquid A;
[0069] (S5), immersing the core package treated with liquid A into the liquid B under negative pressure for 8 minutes, and then performing vacuum drying to obtain a core package treated with liquid B;
[0070] (S6), one step (S4) and one step (S5) are recorded as one cycle, and the cycle operation is performed 6 times, and after each cycle, the core is immersed in ethanol for 8 minutes, and then vacuum dried to obtain a solid capacitor.
[0071] In the step (S3), the immersion height of the wound capacitor core package is less than one third of the distance from the top of the wound capacitor core package, the heat drying treatment is air drying at 150°C for 50 minutes, and the second heat drying treatment is air drying at 150°C for 25 minutes.
[0072] In the step (S4), the immersion height of the anti-corrosion core package is lower than half of the distance from the top of the anti-corrosion core package, and the immersion condition is a negative pressure of -0.09MPa; when the anti-corrosion core package is taken out after impregnation, the droplets hanging at the bottom of the anti-corrosion core package are scraped off; the pre-drying treatment is pre-drying at 60°C with forced air for 20 minutes; the vacuum drying treatment is drying at 150°C in a vacuum drying oven for 8 minutes.
[0073] In the step (S5), the impregnation height of the core package treated with liquid A is the same as the impregnation height in step (S4), and the immersion condition is a negative pressure of -0.09 MPa; the vacuum drying treatment is drying in a vacuum drying oven at 125°C for 6 minutes.
[0074] In the step (S6), the vacuum drying treatment is carried out by drying in a vacuum drying oven at 150° C. for 5 minutes.
[0075] The benzofurandione monomer is 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione; the solvent A is dimethyl sulfoxide; and the conductive polymer solution is a conductive polymer PBFDO-dimethyl sulfoxide solution with a solid content of 15 mg / ml.
[0076] The mass ratio of the benzofurandione monomer to the conductive polymer is 18:1; the concentration of the benzofurandione monomer after being dissolved in solvent A is 25 mg / ml.
[0077] The oxidant is benzoyl peroxide; and the pretreatment solution is PVDF solution.
[0078] The solvent B is dimethyl sulfoxide; the concentration of the B solution is 25 mg / ml.
[0079] Example 4
[0080] A method for preparing a solid capacitor comprises the following steps:
[0081] (S1), mixing a benzofurandione monomer and a solvent A and heating to dissolve, then adding a conductive polymer solution and stirring evenly to obtain a liquid A;
[0082] (S2), taking the oxidant and the solvent B and mixing them evenly to obtain liquid B;
[0083] (S3), taking the wound capacitor core package, after heat drying to remove water, placing it in the pretreatment liquid for immersion, the immersion time is 8 minutes, taking out the wound capacitor core package and heat drying it again to obtain an anti-corrosion core package;
[0084] (S4), immersing the anti-corrosion core package in the liquid A under negative pressure for 8 minutes, taking out the anti-corrosion core package, pre-drying it, and then vacuum drying it to obtain a core package treated with liquid A;
[0085] (S5), immersing the core package treated with liquid A into the liquid B under negative pressure for 5 minutes, and then performing vacuum drying to obtain a core package treated with liquid B;
[0086] (S6), record one step (S4) and one step (S5) as one cycle, and repeat the operation three times. After each cycle, the core is immersed in ethanol for 5 minutes, and then vacuum dried to obtain a solid capacitor.
[0087] In the step (S3), the immersion height of the wound capacitor core package is less than half of the distance from the top of the wound capacitor core package, the heat drying treatment is forced air drying at 150°C for 40 minutes, and the second heat drying treatment is forced air drying at 150°C for 40 minutes.
[0088] In the step (S4), the immersion height of the anti-corrosion core package is lower than half of the distance from the top of the anti-corrosion core package, and the immersion condition is a negative pressure of -0.08MPa; when the anti-corrosion core package is taken out after impregnation, the droplets hanging at the bottom of the anti-corrosion core package are scraped off; the pre-drying treatment is pre-drying at 60°C with forced air for 12 minutes; the vacuum drying treatment is drying at 100°C in a vacuum drying oven for 12 minutes.
[0089] In the step (S5), the impregnation height of the core package treated with liquid A is the same as the impregnation height in step (S4), and the immersion condition is a negative pressure of -0.08 MPa; the vacuum drying treatment is drying in a vacuum drying oven at 100°C for 40 minutes.
[0090] In the step (S6), the vacuum drying treatment is carried out by drying in a vacuum drying oven at 100° C. for 12 minutes.
[0091] The benzofurandione monomer is 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione; the solvent A is a mixture of dimethyl sulfoxide and N,N-dimethylacetamide in a weight ratio of 1:1; and the conductive polymer solution is a conductive polymer PBFDO-dimethyl sulfoxide solution with a solid content of 14 mg / ml.
[0092] The mass ratio of the benzofurandione monomer to the conductive polymer is 10:1; the concentration of the benzofurandione monomer after being dissolved in solvent A is 20 mg / ml.
[0093] The oxidant is potassium persulfate; and the pretreatment solution is PVDF solution.
[0094] The solvent B is deionized water; the concentration of the B solution is 20 mg / ml.
[0095] Comparative Example 1
[0096] In this comparative example, the wound capacitor core package is not subjected to the pre-treatment liquid impregnation operation.
[0097] Specifically:
[0098] A method for preparing a solid capacitor comprises the following steps:
[0099] (S1), mixing a benzofurandione monomer and a solvent A and heating to dissolve, then adding a conductive polymer solution and stirring evenly to obtain a liquid A;
[0100] (S2), taking the oxidant and the solvent B and mixing them evenly to obtain liquid B;
[0101] (S3), taking the wound capacitor core package, and removing water through heat drying to obtain a dry core package;
[0102] (S4), immersing the dry core package in the liquid A under negative pressure for 5 minutes, taking out the dry core package, pre-drying it, and then vacuum drying it to obtain a core package treated with liquid A;
[0103] (S5), immersing the core package treated with liquid A into the liquid B under negative pressure for 5 minutes, and then performing vacuum drying to obtain a core package treated with liquid B;
[0104] (S6), record one step (S4) and one step (S5) as one cycle, and repeat the operation 4 times. After each cycle, the core is immersed in ethanol for 5 minutes, and then vacuum dried to obtain a solid capacitor.
[0105] In the step (S3), the heat drying treatment is performed by forced air drying at 150°C for 30 minutes.
[0106] In the step (S4), the immersion height of the dry core package is lower than two-fifths of the distance from the anti-corrosion core package to the top, and the immersion condition is a negative pressure of -0.08MPa; when the dry core package is taken out after impregnation, the droplets hanging on the bottom of the dry core package are scraped off; the pre-drying treatment is pre-drying at 60°C with forced air for 12 minutes; the vacuum drying treatment is drying at 110°C in a vacuum drying oven for 10 minutes.
[0107] In the step (S5), the impregnation height of the core package treated with liquid A is the same as the impregnation height in step (S4), and the immersion condition is a negative pressure of -0.08 MPa; the vacuum drying treatment is drying in a vacuum drying oven at 95°C for 25 minutes.
[0108] In the step (S6), the vacuum drying treatment is carried out by drying in a vacuum drying oven at 100° C. for 10 minutes.
[0109] The benzofurandione monomer is 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione; the solvent A is dimethyl sulfoxide; and the conductive polymer solution is a conductive polymer PBFDO-dimethyl sulfoxide solution with a solid content of 10.6 mg / ml.
[0110] The mass ratio of the benzofurandione monomer to the conductive polymer is 10:1; the concentration of the benzofurandione monomer after being dissolved in solvent A is 15 mg / ml.
[0111] The oxidant is 2,5-dimethylbenzoquinone.
[0112] The solvent B is dimethyl sulfoxide; the concentration of the B solution is 20 mg / ml.
[0113] Comparative Example 2
[0114] A method for preparing a solid capacitor comprises the following steps:
[0115] (S1), mixing a benzofurandione monomer and a solvent A and heating to dissolve, then adding a conductive polymer solution and stirring evenly to obtain a liquid A;
[0116] (S2), taking the oxidant and the solvent B and mixing them evenly to obtain liquid B;
[0117] (S3), taking the wound capacitor core package, after heat drying to remove water, placing it in the pretreatment liquid for immersion, the immersion time is 6 minutes, taking out the wound capacitor core package and heat drying it again to obtain an anti-corrosion core package;
[0118] (S4), immersing the anti-corrosion core package in the liquid A at normal pressure for 5 minutes, taking out the anti-corrosion core package, pre-drying it, and then vacuum drying it to obtain a core package treated with liquid A;
[0119] (S5), immersing the core package treated with the liquid A into the liquid B at normal pressure for 5 minutes, and then performing vacuum drying to obtain a core package treated with the liquid B;
[0120] (S6), record one step (S4) and one step (S5) as one cycle, and repeat the operation 4 times. After each cycle, the core is immersed in ethanol for 5 minutes, and then vacuum dried to obtain a solid capacitor.
[0121] In the step (S3), the immersion height of the wound capacitor core package is lower than two-fifths of the distance from the top of the wound capacitor core package, the heat drying treatment is air drying at 150°C for 30 minutes, and the second heat drying treatment is air drying at 150°C for 30 minutes.
[0122] In the step (S4), the immersion height of the anti-corrosion core package is lower than two-fifths of the distance from the top of the anti-corrosion core package; when the anti-corrosion core package is taken out after impregnation, the droplets hanging at the bottom of the anti-corrosion core package are scraped off; the pre-drying treatment is pre-drying at 60°C with forced air for 12 minutes; the vacuum drying treatment is drying at 110°C in a vacuum drying oven for 25 minutes.
[0123] In the step (S5), the impregnation height of the core package treated with liquid A is the same as the impregnation height in step (S4); the vacuum drying treatment is carried out by drying in a vacuum drying oven at 95°C for 25 minutes.
[0124] In the step (S6), the vacuum drying treatment is carried out by drying in a vacuum drying oven at 100° C. for 10 minutes.
[0125] The benzofurandione monomer is 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione; the solvent A is dimethyl sulfoxide; and the conductive polymer solution is a conductive polymer PBFDO-dimethyl sulfoxide solution with a solid content of 10.6 mg / ml.
[0126] The mass ratio of the benzofurandione monomer to the conductive polymer is 10:1; the concentration of the benzofurandione monomer after being dissolved in solvent A is 15 mg / ml.
[0127] The oxidant is 2,5-dimethylbenzoquinone; and the pretreatment solution is PVDF solution.
[0128] The solvent B is dimethyl sulfoxide; the concentration of the B solution is 20 mg / ml.
[0129] Performance Testing
[0130] Take the solid capacitors of Examples 1-4 and Comparative Examples 1-2, and use the ZX8516B-1X series multi-parameter multi-frequency tester to test, calculate / record the capacity extraction rate, DF value, ESR value, and the capacity decay after 125℃*2000h load; use the ZX6589-800V capacitor leakage current tester to test and record the LC value. Among them, the capacity extraction rate = actual test capacity CpY / standard capacity * 100%; the capacity decay is the capacity change rate before and after 125℃*2000h load treatment. The test results are shown in Table 1 below:
[0131]
[0132] It can be seen from Table 1 above that the solid capacitor of the present invention has a higher extraction rate, a lower ESR and better heat resistance.
[0133] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A method for preparing a solid capacitor, characterized in that: The steps include: (S1), mixing a benzofurandione monomer and a solvent A and heating to dissolve, then adding a conductive polymer solution and stirring evenly to obtain a liquid A; (S2), taking the oxidant and the solvent B and mixing them evenly to obtain liquid B; (S3), taking the wound capacitor core package, subjecting it to heat drying treatment to remove water, and then placing it in the pretreatment liquid for immersion, the immersion time is 2-10min, taking out the wound capacitor core package and subjecting it to heat drying treatment again to obtain an anti-corrosion core package; (S4), immersing the anti-corrosion core package in the liquid A under negative pressure for 1-10 minutes, taking out the anti-corrosion core package, pre-drying it, and then vacuum / air drying it to obtain a core package treated with liquid A; (S5), immersing the core package treated with liquid A into the liquid B under negative pressure for 1-8 minutes, and then performing vacuum / air drying to obtain a core package treated with liquid B; (S6), steps (S4) and (S5) are recorded as one cycle, and the cycle is performed 2-6 times, and after each cycle, the core is immersed in ethanol for 3-8 minutes, and then vacuum / air drying is performed to obtain a solid capacitor.
2. The method for preparing a solid capacitor according to claim 1, characterized in that: In the step (S3), the immersion height of the wound capacitor core package is lower than one third to one half of the distance from the top of the wound capacitor core package, the heat drying treatment is forced air drying at 150°C for 25-50 minutes, and the second heat drying treatment is forced air drying at 150°C for 25-50 minutes.
3. The method for preparing a solid capacitor according to claim 1, characterized in that: In the step (S4), the immersion height of the anti-corrosion core bag is lower than one third to one half of the distance from the top of the anti-corrosion core bag, and the immersion condition is a negative pressure of -0.06 to -0.09 MPa; when the anti-corrosion core bag is taken out after impregnation, the droplets hanging at the bottom of the anti-corrosion core bag are scraped off; The pre-drying treatment is to dry at 60°C with forced air for 5-20 minutes; the vacuum / force air drying treatment is to dry at 80-150°C in a vacuum / force air drying oven for 10-50 minutes.
4. The method for preparing a solid capacitor according to claim 1, characterized in that: In the step (S5), the impregnation height of the core package treated with liquid A is the same as the impregnation height in step (S4), and the immersion condition is a negative pressure of -0.06 to -0.09 MPa; the vacuum / blast drying treatment is carried out by drying in a vacuum / blast drying oven at 60-125°C for 5-50 minutes.
5. The method for preparing a solid capacitor according to claim 1, characterized in that: In the step (S6), the vacuum / air drying treatment is carried out in a vacuum / air drying oven at 60-150° C. for 5-20 minutes.
6. The method for preparing a solid capacitor according to claim 1, characterized in that: The benzofurandione monomer is 3,7-dihydrobenzo[1,2-b:4,5-b']difuran-2,6-dione; the solvent A is at least one of dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile and propylene carbonate; the conductive polymer solution is a conductive polymer PBFDO-dimethyl sulfoxide solution, PBFDO-N,N-dimethylacetamide solution, PBFDO-N,N-dimethylformamide solution or PBFDO-N-methylpyrrolidone solution with a solid content of 6-15 mg / ml.
7. The method for preparing a solid capacitor according to claim 1, characterized in that: The mass ratio of the benzofurandione monomer to the conductive polymer is 1-20:1; the concentration of the benzofurandione monomer after being dissolved in solvent A is 4-25 mg / ml.
8. The method for preparing a solid capacitor according to claim 1, characterized in that: The oxidant is at least one of organic quinones, phosphomolybdic acid, peroxides, metal salts, persulfates, metal oxides, non-metal oxides, perborate and perbenzoic acid compounds.
9. The method for preparing a solid capacitor according to claim 1, characterized in that: The solvent B is at least one of dimethyl sulfoxide, ethanol, ethyl acetate, N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, deionized water, acetonitrile and propylene carbonate; the concentration of the B solution is 2-100 mg / ml.
10. A solid capacitor, characterized in that: The solid-state capacitor is prepared by the preparation method of any one of claims 1 to 9.
